Idiolek Penggunaan Bahasa Thailand ke dalam Bahasa Indonesia pada Mahasiswa Thailand di Universitas Muhammadiyah Tangerang - Sumiyani Sumiyani (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2019)
The purpose of this study was to describe idiolects use of Thai language into Indonesian. The research method uses descriptive qualitative methods with content analysis techniques. The technique of collecting data uses interviewing techniques and note-taking techniques. The researcher observed and analyzed the results of data collection using the extralingual equivalent method, by examining the pronunciation (phonology) of students when speaking in good and correct Indonesian. The results of the study showed that Thai students in the pronunciation of everyday language using Indonesian were good enough. However, if viewed from a linguistic point of view, there are still errors in pronunciation and are still halting in saying words because they are influenced by the Thai dialect. The results of this study can be used as evaluations in second language learning especially foreign student learners.